Pelatihan Safety Management System Bagi Personel Penerbangan Bidang Pelayanan Lalu Lintas Penerbangan - Dwi Lestary; Aswia, Pangsa Rizkina; Jatmoko, Djoko; Adiliawijaya, Rany; Handayantri, Dhiayu (Jurnal Pengabdian Kepada Masyarakat, 2022)
Aviation safety is the business and responsibility of all parties, not only in theory but also in practice, through a continuous process of identifying hazards, managing risks, and performance expectations. Safety Management System training is mandatory training for all aviation personnel as stated in the Regulation of the Minister of Transportation of the Republic of Indonesia PM No. 62 of 2017 (Civil Aviation Safety Regulation Part 19) concerning Safety Management Systems. The increasingly fierce job competition requires every individual to have competence and knowledge as complete as possible, so with this training, it is hoped that graduates of PPI Curug in the field of Air Traffic Services can compete in the world of work and get one of the most important and mandatory training in the aviation world, namely the safety management system. Community Service Activities (PKM) Safety Management System Training for Air Traffic Services Personnel will be carried out online through the online meeting application, namely ZOOM. Participants are PPI Curug alumni in the ATS field who do not have SMS training certificates, totaling 37 people. It is hoped that the PKM PPI Curug activities will give the participants useful skills and training, as well as give both the participants and the teachers experience.